Pathophysiology and clinical characteristics of hypothalamic obesity in children and adolescents - Ja Hye Kim; Jin-Ho Choi (Korean Society of Pediatric Endocrinology, 2013)
The hypothalamus plays a key role in the regulation of body weight by balancing the intake of food, energy expenditure, and body fat stores, as evidenced by the fact that most monogenic syndromes of morbid obesity result from mutations in genes expressed in the hypothalamus. Hypothalamic obesity is a result of impairment in the hypothalamic regulatory centers of body weight and energy expenditure, and is caused by structural damage to the hypothalamus, radiotherapy, Prader-Willi syndrome, and mutations in the LEP, LEPR, POMC, MC4R and CART genes. The pathophysiology includes loss of sensitivity to afferent peripheral humoral signals, such as leptin, dysregulated insulin secretion, and impaired activity of the sympathetic nervous system. Dysregulation of 11β-hydroxysteroid dehydrogenase 1 activity and melatonin may also have a role in the development of hypothalamic obesity. Intervention of this complex entity requires simultaneous targeting of several mechanisms that are deranged in patients with hypothalamic obesity. Despite a great deal of theoretical understanding, effective treatment for hypothalamic obesity has not yet been developed. Therefore, understanding the mechanisms that control food intake and energy homeostasis and pathophysiology of hypothalamic obesity can be the cornerstone of the development of new treatments options. Early identification of patients at-risk can relieve the severity of weight gain by the provision of dietary and behavioral modification, and antiobesity medication. This review summarizes recent advances of the pathophysiology, endocrine characteristics, and treatment strategies of hypothalamic obesity.